Precipitation Synthesis of CeO2 Nanopowder Pigment - Iis Nurhasanah; Yayuk Astuti; Pandji Triadiyaksa (Jurnal Rekayasa Kimia & Lingkungan, 2023)
Nanopowder pigments of CeO2 and CeO2:Fe were synthesized by precipitation method at a moderate calcination temperature of 500oC.  The pigments exhibited pale yellow for CeO2 nanopowder and brick red for CeO2:Fe nanopowder.  Both pigments possessed mesoporous and cubic fluorite structures of CeO2.  The incorporation of Fe into CeO2 reduced crystallite size and increased surface area. Moreover, it widens bandgap energy and significantly improved the absorption property of CeO2 nanopowder.